Professional Zakat Collection Management at Baitul Mal Aceh - Mohammad Haikal; Sumardi Efendi (Jurnal Internasional Ekonomi Islam, 2023)
In line with the developments in the era of human life, especially in the economic field, earning activities through skills and professions will continue to grow from time to time. The determination of professional zakat obligations to him shows that Islamic law is very aspirational and responsive to the times. The Baitul Mal Institution works to manage zakat, religious assets, and other assets, so using field research methods the researcher wants to see the management of professional zakat collection at Baitul Mal Aceh, from the research results it is concluded that the professional zakat collection system at Baitul Mal Aceh is carried out with the first system, you can go to the counter to record your name and then provide a receipt for proof of zakat payment, secondly, you can go through a bank account via the mobile banking application to deliver the zakat/zakat deposit, after the zakat is paid, we will send it to the regional treasury, as for the account number. As for the opportunities and obstacles in collecting professional zakat, namely, the opportunity is that there is still public trust in the management of zakat carried out by Baitul Mal Aceh so that it is motivated to be better, with this opportunity the Baitul Mal continues to strive to increase professional zakat collection.